2009
DOI: 10.1136/bjo.2009.161729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Lenstar LS 900 non-contact biometer

Abstract: The reproducibility of the Lenstar was excellent. Small but significant differences exist between the Lenstar, Visante OCT and the IOLMaster. Therefore, measurements of the Lenstar, AS-OCT and IOLMaster are not interchangeable. Despite the significant difference between AL measurements, there is no clinically significant difference in the IOL power calculation results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
5
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 15 publications
10
119
5
7
Order By: Relevance
“…Therefore, lens thickness may be greater in HD patients than in healthy patients. Pre-HD lens thickness was approximately 4.52 mm in our patients, which is comparable to that measured by Shammas and Hoffer 15 and thicker than that measured by Cruysberg et al 14 It should be noted that patients in the latter study were, on average, 25.9 years younger than our patients. This is relevant because our data showed that lens thickness was highly correlated with subject age.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, lens thickness may be greater in HD patients than in healthy patients. Pre-HD lens thickness was approximately 4.52 mm in our patients, which is comparable to that measured by Shammas and Hoffer 15 and thicker than that measured by Cruysberg et al 14 It should be noted that patients in the latter study were, on average, 25.9 years younger than our patients. This is relevant because our data showed that lens thickness was highly correlated with subject age.…”
Section: Discussionsupporting
confidence: 86%
“…Cruysberg et al 14 . Similarly, we found a 0.041 mm difference of the axial length after HD and IOL power difference of approximately 0.05 D. Although, the difference in AL is statistically significant, it has a small effect size (Cohen's d ¼ 0.06) which decreases the clinical significance of the axial length differences.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, all variables and the corneal power were normally distributed in the population, which differs from the results of previous studies [15]. The mean AL in the Chinese study was longer than in the current and some previous studies and appears to be closely associated with genetic and environmental Factors [16].…”
Section: Discussioncontrasting
confidence: 99%
“…2 In the case of the Lenstar (Haag-Streit, Koeniz, Switzerland), the interclass coefficient of the variation of the astigmatism axis was 0.915 and the mean arithmetic difference between the two measurement sessions was 3.19°, with an absolute difference of a median of 9°. 5 The Lenstar keratometry has repeatable values, 6,7 but according to Zhao et al, 7 the Lenstar and the IOLMaster cannot be used interchangeably in relation to keratometric data. With regard to average keratometric data, it seems that the Lenstar is biometrically equivalent to the IOLMaster, 8 and the correlation between the cylinder axis measurements of the IOLMaster and the Lenstar is high.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%